Changes in metabolic parameters in ischemic heart disease against the background of metabolic syndrome - Akimova, Viorika; Demianchuk, Nataliia; Shchurko, Mariia; Lapovets, Lyubov; Valovyi, Oleksii (ScienceRise: Medical Science, 2023)
For many years, and to this day, cardiovascular disease has been and remains the leading cause of death worldwide. Cardiovascular diseases mainly affect people in countries with middle and low living standards. The aim of the study was to find out the peculiarities of lipid, carbohydrate, and hormonal changes in patients with coronary heart disease against the background of metabolic syndrome. Materials and methods: 120 patients with verified coronary heart disease were examined, including 60 patients with coronary heart disease without metabolic syndrome and 60 patients with coronary heart disease with metabolic syndrome. The control group consisted of 30 practically healthy individuals of appropriate age and sex. The content of HbA1c, glucositol C-peptide, triacylglycerols, total cholesterol, leptin, HDL-cholesterol, and LDL-cholesterol in blood serum was determined by modern methods. Results: The analysis of the results of laboratory tests of patients’ blood revealed more pronounced changes in carbohydrate and lipid metabolism in patients with coronary artery disease against the background of metabolic syndrome, which indicates the severity of the clinical course in such patients. The results obtained indicate that in coronary heart disease with metabolic syndrome, there are more pronounced dysmetabolic changes: hyperleptinemia, glucosemia, elevated HbA1c, and decreased C-peptide content. Studies have shown that obesity is accompanied by high levels of leptin, which exacerbates insulin resistance and is a trigger for the development of coronary heart disease. Conclusions: 1. Leptin resistance is a potential cause of insulin resistance and, consequently, obesity, which ultimately leads to metabolic syndrome and the development of coronary heart disease. The data obtained indicate a greater tendency to obesity in women with coronary heart disease complicated by metabolic syndrome. The data obtained may indicate a latent disorder of carbohydrate metabolism in patients with coronary artery disease without metabolic syndrome. The detected deviations in lipid metabolism indicate the presence of type II dyslipoproteinemia in patients of group 1 and type IV dyslipoproteinemia in patients of group 2